"This is Not Who We Are": Students Leading for Anti-Racist Policy Changes in Alexandria City Public Schools, Virginia. Issue 1 (January 2022) - Mansfield, Katherine Cumings; Lambrinou, Marina
This paper centers the voices of students who successfully struggled alongside justice-minded school board members and other concerned citizens to create anti-racist policy changes in Alexandria City Public Schools, Virginia. Specifically, we examine the history behind, and political processes involved with, changing the names of two local schools due to the racist political commitments of their namesakes. Lessons learned include the need to carefully structure the policy change process to include students, families, and other community members in critical dialog and amplify the voices of those most impacted by the structural racism that needs to be dismantled: The students.